The effect of the WHO Safe Childbirth Checklist on essential delivery practices and birth outcomes: Evidence from a pair-wise matched randomized controlled trial in Pakistan - Jana Kuhnt; Ashfa Hashmi; Sebastian Vollmer (SSM: Population Health, 2023)
We study the effect of the Safe Childbirth Checklist (SCC) – a tool developed by the WHO to improve the quality of delivery care – on a range of provider- and patient-level outcomes. We conducted a clustered pair-wise matched randomized controlled trial among 166 health providers in two districts of Pakistan. This included primary and secondary health facilities as well as non-facility based rural health workers. We do not find positive effects on health outcomes, but on the adherence to some essential delivery practices, mostly to those conducted during the patient's admission to the delivery ward. We also find increased rates of referrals to higher-level facilities.